Sedimentology and Provenance of NE Australian Proterozoic Basins with Relevance to the Formation of the Supercontinent Nuna - Nordsvan, Adam Richmond (Curtin University, 2019)
Roughly 1.6 billion years ago NE Australia was connected to North America. In this thesis, rocks in Queensland are examined to understand this connection and with relevance to the supercontinent Nuna. Findings suggest that a large part of NE Australia is actually a piece of North America that was transferred during supercontinent assembly.